Diastolic Blood Pressure Threshold During Pediatric Cardiopulmonary Resuscitation and Survival Outcomes: A Multicenter Validation Study*. Issue 1 (9th November 2022) - Berg, Robert A.; Morgan, Ryan W.; Reeder, Ron W.; Ahmed, Tageldin; Bell, Michael J.; Bishop, Robert; Bochkoris, Matthew; Burns, Candice; Carcillo, Joseph A.; Carpenter, Todd C.; Dean, J. Michael; Diddle, J. Wesley; et al.
Abstract : OBJECTIVES: Arterial diastolic blood pressure (DBP) greater than 25 mm Hg in infants and greater than 30 mm Hg in children greater than 1 year old during cardiopulmonary resuscitation (CPR) was associated with survival to hospital discharge in one prospective study. We sought to validate these potential hemodynamic targets in a larger multicenter cohort. DESIGN: Prospective observational study. SETTING: Eighteen PICUs in the ICU-RESUScitation prospective trial from October 2016 to March 2020. PATIENTS: Children less than or equal to 18 years old with CPR greater than 30 seconds and invasive blood pressure (BP) monitoring during CPR. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Invasive BP waveform data and Utstein-style CPR data were collected, including prearrest patient characteristics, intra-arrest interventions, and outcomes. Primary outcome was survival to hospital discharge, and secondary outcomes were return of spontaneous circulation (ROSC) and survival to hospital discharge with favorable neurologic outcome. Multivariable Poisson regression models with robust error estimates evaluated the association of DBP greater than 25 mm Hg in infants and greater than 30 mm Hg in older children with these outcomes. Among 1, 129 children with inhospital cardiac arrests, 413 had evaluable DBP data. Overall, 85.5% of the patients attained thresholds of mean DBP greater than or equal to 25 mm Hg in infants and greater than or equal to 30 mm Hg in older children. Initial return of circulation occurred in 91.5% and 25% by placement on extracorporeal membrane oxygenator. Survival to hospital discharge occurred in 58.6%, and survival with favorable neurologic outcome in 55.4% (i.e. 94.6% of survivors had favorable neurologic outcomes). Mean DBP greater than 25 mm Hg for infants and greater than 30 mm Hg for older children was significantly associated with survival to discharge (adjusted relative risk [aRR], 1.32; 1.01–1.74; p = 0.03) and ROSC (aRR, 1.49; 1.12–1.97; p = 0.002) but did not reach significance for survival to hospital discharge with favorable neurologic outcome (aRR, 1.30; 0.98–1.72; p = 0.051). CONCLUSIONS: These validation data demonstrate that achieving mean DBP during CPR greater than 25 mm Hg for infants and greater than 30 mm Hg for older children is associated with higher rates of survival to hospital discharge, providing potential targets for DBP during CPR.